Impact of early intervention of speech and language therapy among hearing impaired child - Kumari, Rina; Tiwari, Sunita; Chatuvedi, Arun; Kumar, Sunil; Rastogi, Nalini (International Journal of Research in Medical Sciences, 2020)
Background: Hearing impairment is a factor that directly compromises the individual’s language which can affect emotional and academic defects by delayed development of communicative ability. This can vary according to the type and degree of hearing loss. Speech therapy intervention is important, along with the use of sound amplification devices, so that the child may have a chance to develop speech, consequently learning and re-habilitation to the society. Aims of the present study was performed to assess the effectiveness of early intervention of speech and language therapy after use of hearing aids to hearing impaired children on their syntactic and lexical development. Methods: This quasi-experimental study conducted on 100 children having different degree of hearing loss at department of Neurology and department of ENT, King George’s Medical University, Lucknow, Uttar Pradesh. After collecting socio-demographic data of subjects by observation, completion of questionnaires, and speech recording by audiologist; Speech and language therapy provide by audiologist for six month after providing hearing aids and improvement in their syntactic and lexical development recorded. Results: There is significant improvement in verbal response from 14% before therapy to 81% after therapy and non-verbal response before therapy was 86% and after therapy was 19%. Before giving speech and language therapy to subjects pointing score was 24%, sign language was 10% and words response was 0% which increases after therapy were 1%, 2% and 39% respectively. Early identified/intervened hearing-impaired children had a notable positive difference in all assessed lingual gains. Conclusions: This is study results definitely point to positive effects of intensive and continuous application of speech and language therapy to syntactic and lexical development of hearing impaired children.